(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the growth and adhesion of microorganisms over the surface of composite resins exposed to different light curing cycles. An in vitro analytical laboratory experimental study of adhesion of yeast and bacteria over the surface of light cured composite resin (Opallis, FGM, Brazil) in continuous and switched modes was carried out (Optilight Max, Dabi Atlante, Brazil) with 1200 mW/cm2 power density. Eighty composite resin discs were produced, randomly divided according to the immersion medium (n=40): TSB broth for bacteria, and Sabouraud dextrose broth for yeast.The samples light-cured in continuous mode had greater adhesion of Candida tropicalis and Staphylococcus aureus, although without statistically significant difference, according to Fisher’s exact test. Based on the findings of the present study, there are no differences in biofilm adhesion on the surface of composite resin restorations regarding the variation of light-curing cycles; in this way, the dental clinician is free to choose the curing cycle that best suits you.